High-Risk Coronary Artery Anomalies, the Cause of Sudden Cardiac Death in Young People - Viren Parmar; Ishmeet Singh; Kunal Duggal; Sarabjeet Singh (Current Overview on Disease and Health Research Vol. 3, 2022)
Sudden Cardiac Death (SCD) syndrome is the second most common cause of high risk coronary anomalies in young people accounting for nearly half a million premature deaths per year. Through this case study we hope to shed light upon and draw awareness on SCD to ultimately help reduce mortality from this condition. SCD has a sudden onset and generally results in death <1 h from presentation of symptoms and can appear in persons without comorbidities that would be deemed fatal [1]. This is why it is imperative that clinicians be aware of this rapidly developing condition and methods to detect it. Our case presents a young, sedentary, symptomatic 34-year-old male who presented to his Primary Care Physician (PCP) with complaints of worsening chest pain. Upon taking the patient’s history, he reported that he was a non-smoker and denied any alcohol or drug use. His family history revealed many incidences of premature coronary artery disease from both his maternal and paternal sides. Much of the research regarding SCD centers around athletes and highly active patient populations. Therefore, this case is especially poignant given the presentation of SCD within a non-athletic and sedentary profile which is an outlier to most literary presentations of SCD.